PREPARATION AND SCALE-UP STUDY OF TREATED FAMOTIDINE FOR THE DEVELOPMENT OF ORALLY DISINTEGRATING TABLETS USING A COMPLEX FLUIDIZED-BED GRANULATOR EQUIPPED WITH A PARTICLE-SIZING MECHANISM - Hosaka, Shouichi; Yamazawa, Masaki; Takahashi, Yoshiteru (International Journal of Current Pharmaceutical Research, 2018)
Objective: Bitter taste-masked drug substance should be needed for the development of orally disintegrating tablets (ODT). We selected a new type of a complex fluidized-bed granulator equipped with a particle-sizing mechanism for treating famotidine (FAM). This study was conducted to demonstrate the critical process parameter, which controls particle size of treated FAM, to determine its acceptable particle size considering uniformity of assay and to perform scale-up study from a laboratory scale to a commercial scale. Methods: Particle size of treated FAM was evaluated by changing spraying air pressure on the operation of a complex fluidized-bed granulator. Uniformity of assay in granules after blending and tablets were compared at different particle size of treated FAM. On the scale-up study, particle size and assay of treated FAM in both scales were evaluated. Results: The particle size of treated FAM decreased as the increase in spraying air pressure in relation to the spraying mist size. Better uniformity of assay was observed when the diameter of treated FAM was 20 µm compared to that of 50 µm. Therefore, target particle size of treated FAM was set at approximately 20 µm. Similar qualities could be obtained between both scales in the points of particle size and assay. Conclusion: On the operation of a complex fluidized-bed granulator, spraying air pressure was the critical process parameter that controlled particle size of treated FAM. On Scale-up study of treated FAM, spraying air pressure in relation to the spraying mist size was important.